2022
DOI: 10.5194/bg-19-2939-2022
|View full text |Cite
|
Sign up to set email alerts
|

Controlling factors on the global distribution of a representative marine non-cyanobacterial diazotroph phylotype (Gamma A)

Abstract: Abstract. Non-cyanobacterial diazotrophs may be contributors to global marine N2 fixation, although the factors controlling their distribution are unclear. Here, we explored what controls the distribution of the most sampled non-cyanobacterial diazotroph phylotype, Gamma A, in the global ocean. First, we represented Gamma A abundance by its nifH quantitative polymerase chain reaction (qPCR) copies reported in the literature and analyzed its relationship to climatological biological and environmental conditions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 98 publications
2
9
1
Order By: Relevance
“…Cosmopolitan distributions were evident for γ-proteobacterial (1G) and cyanobacterial diazotrophs (1B; Fig. 8a), corroborating and extending previous findings (Farnelid et al, 2011; Shao and Luo, 2022; Halm et al, 2012; Fernandez et al, 2011; Löscher et al, 2014; Cheung et al, 2016). At low to mid latitudes, γ- proteobacterial (1G) diazotrophs generally had high relative abundances and were often the dominant taxa when present.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Cosmopolitan distributions were evident for γ-proteobacterial (1G) and cyanobacterial diazotrophs (1B; Fig. 8a), corroborating and extending previous findings (Farnelid et al, 2011; Shao and Luo, 2022; Halm et al, 2012; Fernandez et al, 2011; Löscher et al, 2014; Cheung et al, 2016). At low to mid latitudes, γ- proteobacterial (1G) diazotrophs generally had high relative abundances and were often the dominant taxa when present.…”
Section: Resultssupporting
confidence: 90%
“…Distinctive pigments and morphologies that enable some cyanobacterial diazotrophs to be identified by microscopy are lacking in many diazotrophs (Carpenter and Capone, 1983; Carpenter and Foster, 2002), including NCDs. Furthermore, many marine diazotrophs are uncultivated, which has required the use of cultivation-independent approaches such as PCR and quantitative PCR (qPCR) (Luo et al, 2012; Shao and Luo, 2022; Turk-Kubo et al, 2022). The nifH gene encodes the identical subunits of the Fe protein of nitrogenase, the enzyme that catalyzes the N 2 fixation reaction, and contains both highly conserved and variable regions enabling its use as a phylogenetic marker and as a proxy for N 2 -fixing potential in marine ecosystems globally (Gaby and Buckley, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, at the global scale, Trichodesmium may be under a weak but stable degree of top‐down control, while the degree of top‐down control on UCYNs varies substantially over space and time (H. Wang & Luo, 2022). Finally, NCDs, which are frequently found in the NPSG, appear to occupy different environmental niches from those of phototrophic cyanobacteria (Cheung et al., 2021; Shao & Luo, 2022), further hindering explanations of the observed distribution of N 2 fixation.…”
Section: N2 Fixation In the Npsgmentioning
confidence: 99%
“…In contrast, Trichodesmium is typically most abundant at low latitudes and decreases northward. No clear latitudinal patterns have been observed for NCD phylotypes (Cheung et al., 2020, 2021; Church et al., 2008; Shao & Luo, 2022; Shiozaki et al., 2017). Notably, however, the distribution of the diazotrophic community shows seasonal variations (see Section 4.3), and because the field surveys were conducted in different seasons, it is likely that the spatial patterns of the diazotrophic community shown here are confounded by seasonal variability (Turk‐Kubo et al., 2023).…”
Section: N2 Fixation In the Npsgmentioning
confidence: 99%
“…S3). A recent study showed that gammaproteobacterial diazotrophs are negatively influenced by temperature during the NEM in the BoB and positively correlated with silicate, suggesting a possible association with diatoms (Shao and Luo 2022). Instead, in the BoB alpha‐ and betaproteobacterial diazotrophs are positively correlated to temperature (Wu et al 2022).…”
Section: Distribution and Diversity Of Diazotrophs In The Indian Oceanmentioning
confidence: 99%